2023
DOI: 10.3390/ma16041534
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Bolometric Performance of Vanadium Oxide Thin Films Modified by Carbon Nanotube Dispersions

Abstract: The influence of carbon nanotube (CNT) dispersions on the electrical properties and noise signal amplitude of VOx films is investigated. For a critical range of the CNT dispersion density on VOx films, the intrinsic properties of the VOx films are modified by the CNTs. The CNT concentrations reported in this work are about 0.3 μg/cm2 and 1.6 μg/cm2, allowing for low density and high density dispersions on the VOx film surface to be investigated. These values are higher than the percolation threshold of about 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In previous studies, numerous methods have been suggested to develop an affordable uncooled microbolometer, employing diverse materials such as Carbon Nanotubes (CNTs) [16][17][18][19][20][21][22][23][24], VO 2 nanowires [25], Germanium nanowires [26], Graphene [27], and spray-coated films consisting of Vanadium Oxide with CNTs [28], among others. While there is a limited body of literature discussing perovskite-based manganite fibers covering their various aspects [29][30][31][32][33][34], there is a significant gap in the literature when it comes to detailing the fabrication of suspended [16,17,28] manganite nanofibers on interdigitated electrodes (IDEs) for infrared sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, numerous methods have been suggested to develop an affordable uncooled microbolometer, employing diverse materials such as Carbon Nanotubes (CNTs) [16][17][18][19][20][21][22][23][24], VO 2 nanowires [25], Germanium nanowires [26], Graphene [27], and spray-coated films consisting of Vanadium Oxide with CNTs [28], among others. While there is a limited body of literature discussing perovskite-based manganite fibers covering their various aspects [29][30][31][32][33][34], there is a significant gap in the literature when it comes to detailing the fabrication of suspended [16,17,28] manganite nanofibers on interdigitated electrodes (IDEs) for infrared sensing applications.…”
Section: Introductionmentioning
confidence: 99%